Analyses of Putative genes involved in the defense mechanism of Gracilaria changii in response to agarase and agarolytic bacteria treatments - Lim, Ee Leen (2014)
Seaweed Gracilaria is the main source of agar worldwide. Information on the induced defense mechanisms of seaweed is scarce, particularly in the aspect of seaweed-microbe interactions. A set of differentially expressed genes from G.changii in response to agarase were generated from a previous study through next generation sequencing of the seaweed transcriptomes. In this study, G. changii was treated with both agarase (which generates the microbe-induced molecular patterns) and a marine agarolytic bacteria, ABS1 isolated from degrading seaweed. The result from the previous study (agarase treatment) was verified and temporal gene expression of candidate genes at 1, 6 and 24 hours post-treatment (hpt) in response to both agarase and bacteria treatments was profiled by quantitative reversetranscription real-time PCR (qRT-PCR). A total of 20 out of 22 candidates verified have the same gene expression patterns as the next generation sequencing result,demonstrating a 90.9% positive correlation between the two analyses. Four candidates encoding plasma membrane calcium-transporting ATPase (GcPMCA),vanadium bromoperoxidase type 1 (GcVBPO1), 3-phosphoshikimate 1-carbpxyvinyltransferase (GcEPSP), and 12-oxophytodienoate reductase (GcOPR) showed more than 2-fold up-regulation compared to that of control samples upon agarase treatment, implying their importance in defense response. The gene encoding vanadium bromoperoxidase type 2 (GcVBPO2) showed more than 2-fold up-regulation compared to that of the control sample upon bacteria treatment. GcVBPO1 and GcVBPO2 displayed different expression profiles in response to the two treatments, indicating the existence of more than one signaling pathways in the transcriptional regulation of vanadium bromoperoxidase. The gene expression of 16 and 10 candidates were further profiled in agarase and bacteria treated samples at different time points, respectively. Most candidates were up-regulated at 1 hpt compared to that of the control sample at the same time point, indicating a rapid modulation of transcription in G. changii upon agarase treatment. The gene expression of these candidates displayed different expression profiles in bacteria treated samples. GcEPSP and GcVBPO2, were found to have the highest fold change when treated by agarase and agarolytic bacteria respectively, at 1 hpt. Temporal gene expression profile of candidates upon agarase and bacteria treatments in G. changii.